2020
DOI: 10.3389/fimmu.2020.02180
|View full text |Cite
|
Sign up to set email alerts
|

CD226 Deletion Reduces Type 1 Diabetes in the NOD Mouse by Impairing Thymocyte Development and Peripheral T Cell Activation

Abstract: The costimulatory molecule CD226 is highly expressed on effector/memory T cells and natural killer cells. Costimulatory signals received by T cells can impact both central and peripheral tolerance mechanisms. Genetic polymorphisms in CD226 have been associated with susceptibility to type 1 diabetes and other autoimmune diseases. We hypothesized that genetic deletion of Cd226 in the non-obese diabetic (NOD) mouse would impact type 1 diabetes incidence by altering T cell activation. CD226 knockout (KO) NOD mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 63 publications
1
36
2
1
Order By: Relevance
“…There is a need for additional studies to determine the impact of rs763361 on CD8 + T cell, Treg and NK cell function specifically. In support of this notion, our group has characterized a novel Cd226 knockout (KO) non‐obese diabetic (NOD) mouse strain, observing attenuated T1D onset with reduced peripheral CD8 + T‐cell activation and avidity of the immunodominant islet‐reactive CD8 + T‐cell specificity, islet‐specific glucose‐6‐phosphatase catalytic subunit‐related protein (IGRP) 34 . Our studies of the impact of CD226 on human Treg function showed that CD226 + TIGIT − Tregs lack Helios expression, have reduced suppressive capacity and increased effector cytokine production, 35 suggesting that the deletion of Cd226 may also provide disease protection via enforcement of Treg lineage stability.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for additional studies to determine the impact of rs763361 on CD8 + T cell, Treg and NK cell function specifically. In support of this notion, our group has characterized a novel Cd226 knockout (KO) non‐obese diabetic (NOD) mouse strain, observing attenuated T1D onset with reduced peripheral CD8 + T‐cell activation and avidity of the immunodominant islet‐reactive CD8 + T‐cell specificity, islet‐specific glucose‐6‐phosphatase catalytic subunit‐related protein (IGRP) 34 . Our studies of the impact of CD226 on human Treg function showed that CD226 + TIGIT − Tregs lack Helios expression, have reduced suppressive capacity and increased effector cytokine production, 35 suggesting that the deletion of Cd226 may also provide disease protection via enforcement of Treg lineage stability.…”
Section: Introductionmentioning
confidence: 99%
“…CD28 binding CD80/CD86, CD27 binding CD70, CD226 binding CD155, OX-40 binding OX-40L, etc.) ( 45 , 46 ). APC such as DC and macrophages serve to initiate T cell responses in the lymph nodes and enhance T cell responses at sites of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 40 Initially, CD226 was described as a key molecule on proinflammatory Th1-differentiated cells and treatment with an α-CD226 monoclonal antibody reduced the onset and severity of disease in experimental autoimmune encephalomyelitis (EAE), an animal model for MS. 40 In the context of autoimmune diabetes, the knockout of CD226 led to a decreased disease severity in the nonobese diabetes mouse model. 41 In humans, genetic variations of CD226 were linked to a higher susceptibility to develop MS and other autoimmune diseases. 42 These findings, together with our data, imply that CD226 is regulated in an age-dependent manner and plays an important role in modulating autoimmunity.…”
Section: Discussionmentioning
confidence: 99%